Physicochemical, microbiological and bioactive evaluations of ‘Araçá-Boi’ (Eugenia stipitata Mc Vaugh) pulp exposed to Gamma Irradiation (Research, Society and Development, 2020)
The aim of this research was to evaluate the physicochemical, microbiological and bioactive quality of ‘Araçá-Boi’ pulps exposed to Gamma Irradiation. Manual harvesting was done in the morning, using good agricultural practices, and fruits were packed in thermal boxes and transported to the ‘Laboratório de Armazenamento e Processamento de Produtos Agrícolas’ of the ‘Universidade Federal de Campina Grande’, to obtain the pulp. The ‘Araçá-Boi’ pulp was irradiated in the ‘Laboratório de Irradiação Gama do Centro de Desenvolvimento de Tecnologia Nuclear’ (CDTN), located at UFPE - Recife, PE, where three doses of Gamma Irradiation (2, 3, 4 kGy) were applied for later comparison with the non-irradiated sample (control). After irradiation, the microbiological, physicochemical parameters and the quantification of vitamin C and flavonoids were evaluated it can be observed that dose 6 is grouped in a set with differential characteristics of the other treatments, as it provided higher AA, pH, luminosity and water activity (Aw). It was observed that there was no microorganism development after irradiation in all analyzed treatments. It can be concluded that the different doses of Gamma Irradiation guaranteed the microbiological quality of the ‘Araçá-Boi’ pulp, remaining fit for consumption and in compliance with the Brazilian legislation.